The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1093/nar/gkr1121
|View full text |Cite
|
Sign up to set email alerts
|

A pre-initiation complex at the 3′-end of genes drives antisense transcription independent of divergent sense transcription

Abstract: The precise nature of antisense transcripts in eukaryotes such as Saccharomyces cerevisiae remains elusive. Here we show that the 3′ regions of genes possess a promoter architecture, including a pre-initiation complex (PIC), which mirrors that at the 5′ region and which is much more pronounced at genes with a defined antisense transcript. Remarkably, for genes with an antisense transcript, average levels of PIC components at the 3′ region are ∼60% of those at the 5′ region. Moreover, at these genes, average le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 39 publications
11
78
0
Order By: Relevance
“…A study in human cells by Conley & Jordan 30 identified many thousands of antisense promoters using CAGE analysis, which characterizes the 5 0 ends of transcripts, and found that such promoters were generally present toward the 3 0 ends of genes. Antisense transcription from these promoters was abundant, though not as high as from sense promoters, in agreement with our findings in yeast, 4 varied between different cell types, and showed evidence of activatory histone marks at their promoters that correlated with the level of RNAPII occupancy. Perhaps most importantly, they found that the activity of sense promoters did not correlate with the levels of activity of their associated antisense promoter.…”
Section: Is Antisense Transcription Prevalent In Mammalian Systems?supporting
confidence: 91%
See 4 more Smart Citations
“…A study in human cells by Conley & Jordan 30 identified many thousands of antisense promoters using CAGE analysis, which characterizes the 5 0 ends of transcripts, and found that such promoters were generally present toward the 3 0 ends of genes. Antisense transcription from these promoters was abundant, though not as high as from sense promoters, in agreement with our findings in yeast, 4 varied between different cell types, and showed evidence of activatory histone marks at their promoters that correlated with the level of RNAPII occupancy. Perhaps most importantly, they found that the activity of sense promoters did not correlate with the levels of activity of their associated antisense promoter.…”
Section: Is Antisense Transcription Prevalent In Mammalian Systems?supporting
confidence: 91%
“…9 Based on this, and the abundant nature of antisense transcription genome-wide, 4 we propose that antisense transcription should be considered a canonical feature of genes, as opposed to an idiosyncrasy particular to just a subset of genes. Future work should seek to understand the function of the dynamic chromatin established by antisense transcription.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations